Runestenen fra Hørning genbelyst - Hertz, Ejvind; M. Imer, Lisbeth (Kuml, 2025)
The Hørning runestone revisited In 1849, farmer Jens Mortensen was ploughing his field when he found a runestone. It has since been known as the Hørning runestone (figs. 1 & 2). Jens Mortensen had the farm from 1809 until 1853. The field, cadastral parcel no. 3, extended from the village all the way northwards to the watercourse Aarhus Å. The text on the Hørning stone The Hørning stone has attracted attention from both archaeological illustrators and runologists since its discovery. The text appears quite straightforward and is translated as ‘Tóki Smith raised the stone in memory of Þorgísl Guðmundr’s son, who gave him gold(?) and freedom’. The final part of the text could, however, also be understood as a reference to Þorgísl Guðmundr’s son’s inclusion of Tóki Smith in his family. There are good examples of both possibilities in the provincial laws and the sagas. Tóki Smith was also behind the Grensten runestone (fig. 3), found near Randers, bearing the text ‘Tóki Smith raised this stone in memory of Hrifli, son of Ásgeirr Bjǫrn’s son. May God help their souls’. The Gylling runestone (fig. 4), found south of Odder, is possibly also linked to Tóki Smith. It bears the text ‘Tóki Þorgísl›s son raised this stone in memory of ... good and risbiik his brother’. Future investigations and 3D scanning of the Gylling runestone may provide data for a more comprehensive understanding of the inscription and a discussion of its relationship to the Hørning and Grensten runestones. The discovery site of the Hørning runestone The exact find site for the runestone is unknown, but several old notes from the National Museum’s archive provide some information on the distance from the bridge Bering Bro and the proximity to two burial mounds. The site can therefore be determined to within an area of c. 50 x 50 m on cadastral no. 3 (figs. 5 & 6). The stone’s subsequent fate In 1849, rural dean Peder Mikkelsen Schinnerup arranged for the runestone to be placed at Hørning church. It was later moved to the church porch before, at some point, being consigned to the cemetery dyke by the road to Aarhus, where it remained until 1873. In 1850, Schinnerup wrote to the Inspector for the Conservation of Antiquarian Monuments in Denmark, J.J.A. Worsaae (fig. 7), saying that the stone would be placed in the church porch. Worsaae saw the stone that same year and gave his first interpretation of the text. In 1852, the office of pastor was taken over by Knud Peter Knudsen (fig. 8), who was not thought to have had any interest in culture or ancient monuments. Via a travelling salesman, Knudsen contacted the museum in Aarhus to hear if they would accept the runestone. His offer was rejected by Professor Lund, the museum director. As the runestone is an ancient monument owned by the state, it could not be moved without authorisation from the National Museum of Denmark in Copenhagen. Knudsen then hired a local haulier to transport the stone to the museum in Aarhus, where there was great surprise when, with no prior warning, the runestone was suddenly unloaded. Worsaae is informed of the situation and writes “To the Society for the Historical-Antiquarian Collection in Aarhus”. “I take the liberty of officially requesting the board of the honourable society to take over the supervision of this stone’s preservation in a safe and suitable place until a more detailed decision on its definitive placement can be made”. This sets the stage for a lengthy clarification and discussion of the actual purpose and function of the runestone. Museum director Professor Lund and curator Vilhelm Boye at the museum in Aarhus are most intent on returning the stone to Hørning church. In a letter from 1873, Boye writes to Worsaae about the difficulties with the stone and the priest in Hørning, “that if one could drink or eat the stone, he (Knudsen) would never have let it go”. Furthermore, he writes that “Professor Lund is very happy that the stone is here and wishes that it may remain in its current location until it can be set up in the new museum, which they probably intend to begin in the spring. His opinion is not that it should become the property of the society, but that it should be entrusted to it for safekeeping forever”. The Hørning runestone remained at the museum in Aarhus and can still be seen today in the Viking Age exhibition at Moesgård Museum. A new runestone in copy The background for the renewed interest in the Hørning runestone is the discovery of the impressive grave of the ‘Viking from Fregerslev’ near Skanderborg in 2012 and local wishes for a copy of the runestone to be erected in Hørning. The ‘Viking from Fregerslev’ was buried in a chamber grave together with a wealth of equipment from his horse, dated to c. AD 950. The grave was excavated in 2017 with overwhelming results. For several years, wishes had been expressed by local groups and individuals for a copy of the Hørning runestone to be erected in the square in Hørning. In response, an accurate copy as possible (fig. 9) was produced by Filip’s stonemasonry in Horsens and rune carver Erik Sandquist and erected in a newly designed square by the church in Hørning. Runestones, their texts and their locations in the landscape are, in themselves, wonderful monuments that take us closer to the people of the Viking Age. They provide a unique opportunity to create brief biographies of the characters who appear in the texts, and thereby contribute to both local history and storytelling in general. Future 3D scans may bring us even closer to Tóki Smith and his contemporaries. Very few runestones have, however, been found in their original location, so it may prove useful to examine the archives thoroughly in the search for a find site. The more pieces that can be assembled in this way, the better the overall story.